Understanding EFL Students' Reading Comprehension Experiences through Vocabulary Knowledge and Reading Motivation: A Systematic Literature Review - Nadziroh Nadziroh; Nailul Authar; Savira Zaniar; Djuwari Djuwari; Tiyas Saputri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This Systematic Literature Review (SLR) investigates how vocabulary knowledge and reading motivation shape English as a Foreign Language (EFL) reading comprehension experiences across secondary and tertiary education levels (Amirah & Wennyta, 2024). Adhering to the PRISMA guidelines, this review synthesizes 20 empirical studies published between 2015 and 2025 sourced from major international databases including Scopus, Web of Science, ERIC, Taylor & Francis, Springer, SAGE, Wiley, and Google Scholar (Amirah & Wennyta, 2024). The synthesis reveals that vocabulary knowledge provides a critical cognitive foundation, acting as a threshold-dependent predictor of text accessibility (Alfiani et al., 2024). Concurrently, reading motivation functions as the primary affective driving force that determines reading engagement and the deployment of self-regulated strategies (Lesiana et al., 2024). The integration of these variables indicates a reciprocal cognitive-affective interaction: rich lexical frameworks enhance task-specific self-efficacy, while high intrinsic motivation prompts sustained engagement with complex vocabulary (Alfiani et al., 2024). Conversely, limitations in these domains lead to cognitive fragmentation, vocabulary constraints, and reading anxiety (Nanda, 2020). This paper identifies critical research gaps, particularly regarding longitudinal moderation dynamics in rural and under-resourced learning environments (Amirah & Wennyta, 2024). It concludes with actionable implications for English Language Teaching (ELT) methodologies, promoting the adoption of balanced, strategy-based instructional designs (Nanda, 2020).